Effective Leadership: From Nature to Vision at SDIT Miftahul Wildan - Muhamad Apit; Nur Muhidin; Titi Maryati; Tamsikuddin; Masduki Dzuriyat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the implementation of transformational leadership by the principal in improving teacher discipline at SDIT Miftahul Wildan. The research employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, then analyzed using the interactive model of Miles and Huberman. The results reveal that the principal effectively applied transformational leadership through four key indicators: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This leadership style successfully fostered a disciplined work environment, motivating teachers to perform their duties effectively. Supporting factors include effective communication, a clear vision, and full support from the principal. However, challenges such as the principal's limited experience and the need for further leadership training were identified. This study recommends strengthening leadership training for principals and enhancing facilities and infrastructure to sustainably support the implementation of transformational leadership.